HALAL BIHALAL IN CULTURAL AND SHARIA PERSPECTIVE: STUDY IN ISLAMIC RELIGIOUS EDUCATION - Sugiana, Yusuf; Rahmat, Rahmat; Erihadiana, Mohamad; Muh Nasir, Tatang (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
The halal bihalal tradition is one of the social customs that are widely practiced by Muslims in Indonesia after Eid al-Fitr. This activity is not only interpreted as forgiving each other, but also as a means to strengthen social relations and strengthen friendship. However, although halal bihalal has become an integral part of Indonesian culture, there are various perceptions regarding the suitability of this practice with the principles of Islamic law. This study aims to analyze halal bihalal from two views: tradition and sharia. Traditionally, halal bihalal is believed to be a moment to strengthen social relations between individuals, but in the aspect of sharia, it is necessary to examine the extent to which this activity is in accordance with Islamic teachings. This study uses a qualitative approach with literature studies and interviews as data collection methods. The results of the study show that although halal bihalal has positive social values, there are elements in this practice that need to be adjusted to the principles of Islamic law. This research provides an understanding of the relationship between Indonesian cultural traditions and Islamic religious teachings, as well as provides directions for the improvement of halal bihalal practices to be more in line with sharia values.